A new WNK4/SYK signaling pathway regulating membrane levels of chloride cotransporters in kidney cells - Loureiro, Cláudia (2014)
Arterial hypertension affects one third of the Western population and constitutes a remarkable risk factor for cardiovascular disease and stroke. Pseudohypoaldosteronism type II or Gordon's syndrome is a rare familial form of hypertension characterized by increased renal salt reabsorption accompanied by hyperkalemia, and caused by mutations in the WNK1 and WNK4 genes. These encode protein kinases regulating renal electrolyte homeostasis through modulation of several membrane transporters and ion channels but the molecular pathways involved are only partially understood. In a recent study on the regulation of the chloride channel CFTR (Cystic Fibrosis Transmembrane Regulator Condutance), a novel WNK4 signaling pathway was described to regulate the amount of CFTR at the cell surface. The underlying mechanism involves tyrosine kinase Syk (Spleen tyrosine kinase), that phosphorylates CFTR protein and promotes its removal from the plasma membrane whereas this activity is inhibited in the presence of WNK4 [1]. In order to study whether the WNK4/Syk interplay may also operate in the regulation of other chloride co-transporters, their protein sequences were inspected for the presence of a Syk consensus motif. Among 20 different transport proteins, the Syk motif was identified only in the sequence of chloride co-transporters NKCC2 and KCC3, which are important for electrolyte homeostasis in the kidney and blood pressure regulation. In order to investigate whether Syk can phosphorylate these channels in vitro, recombinant NKCC2 and KCC3 fragments were produced and tested as substrates in in vitro phosphorylation assays. Strong phosphorylation of renal channels NKCC2 and KCC3 by Syk was observed. The results of this study are a first step to understand the regulation of these ion channels via the WNK4/Syk pathway and possible identify a new mode regulating electrolyte homeostasis in the kidney, potentially related to hypertension.